THE ROLE OF BUSINESS COMMUNICATION IN IMPROVING EMPLOYEE PERFORMANCE AT CAMILLE BEAUTY - Wulan Alviena Putri Utami; Isnaeny Noer Oktavia Hanif; Nabila Rahma Yunita; Devira Vianti Putri; Arkan Naufal; Ricky Firmansyah (Lembaga Riset dan Inovasi Kreyat Center, 2023)
Good communication will create a harmonious working atmosphere and can reduce conflicts between employees so that the company will create morale that improves employee performance for the better. If communication is not well established, there will be a problem between employees. The method used in this research is a literature study. The purpose of this study is to determine the role of business communication in improving the performance of Camille Beauty employees. The method used in this research is a literature study. The purpose of this study is to determine the role of business communication in improving the performance of Camille Beauty employees. The results of this study show that the implementation of Camille Beauty's communication role has succeeded in improving employee performance. For Camille Beauty, the role of business communication is a communication role that includes various stages of continuous, variable, and nonstop communication within the framework of delivering messages. Since the messages sent and received have an influence on each other, communication is the opposite process. In order to improve good employee performance, Ambassador employees at Camille Beauty must be aware of and able to implement the Guest Service Cycle (GSC) as an operational standard for the employee service cycle. At Camille Beauty, employee performance refers to the quality and quantity of work performed by an employee in accordance with the responsibilities given a real achievement. In this case, researchers focused more on the quality of the results produced by Camille Beauty employees.